Cost-effectiveness analysis of replacing the 10-valent pneumococcal conjugate vaccine (PCV10) with the 13-valent pneumococcal conjugate vaccine (PCV13) in Brazil infants. Issue 4 (3rd April 2021) - Perdrizet, Johnna; Santana, Carlos Felipe S.; Senna, Thais; Alexandre, Rodrigo Fernandes; Sini de Almeida, Rodrigo; Spinardi, Julia; Wasserman, Matt
ABSTRACT: Brazil currently has a 10-valent pneumococcal conjugate vaccine (PCV10) pediatric national immunization program (NIP). However, in recent years, there has been significant progressive increases in pneumococcal disease attributed to serotypes 3, 6A, and 19A, which are covered by the 13-valent PCV (PCV13). We sought to evaluate the cost-effectiveness and budget impact of switching from PCV10 to PCV13 for Brazilian infants from a payer perspective. A decision-analytic model was adapted to evaluate the clinical and economic outcomes of continuing PCV10 or switching to PCV13. The analysis estimated future costs (BRL), quality-adjusted life-years (QALYs), and health outcomes for PCV10 and PCV13 over 5 y. Input parameters were from published sources. Future serotype dynamics were predicted using Brazilian and global historical trends. Over 5 y, PCV13 could prevent 12, 342 bacteremia, 15, 330 meningitis, 170, 191 hospitalized pneumonia, and 25, 872 otitis media cases, avert 13, 709 pneumococcal disease deaths, gain 20, 317 QALYs, and save 172 million direct costs compared with PCV10. The use of PCV13 in the Brazilian NIP could reduce pneumococcal disease, improve population health, and save substantial health-care costs. Results are reliable even when considering uncertainty for possible serotype dynamics with different underlying assumptions.